PENGARUH KEPUTUSAN PENDANAAN, KEBIJAKAN DEVIDEN DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Hadi Sumarsono (Universitas Muhammadiyah Ponorogo, 2016)
This research examines the effect of financing decisions, dividend policy and growth to firm value. This study used 30 firm-year samples of firms listed in Indonesian Stock Exchange during 2008. Sampling method uses purposive sampling method. Data analysis technique uses classic assumption test: multicolinierity test, autocorrelation test, and heteroscedasticity test,. Hypothesis test uses multiple regression analysis. The result of this research indicated that financing decisions negatively not significant affects the firm value. The effect of dividend policy and growth to firm value are positively significant.